2013
DOI: 10.1097/qco.0b013e32835c2120
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted hepatitis C infection

Abstract: An improved understanding of HCV epidemiology will allow implementation of more effective public health interventions to limit onward transmission of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 70 publications
6
83
0
3
Order By: Relevance
“…Infections in HIV-infected individuals were predominately due to genotype 1a viruses and found only in males possibly reflecting un-reported sex between men. In addition to drug use, the observation of transmission in known HIV positives is not surprising with recent studies from high income countries have demonstrated a high incidence of recent HCV infections in HIV-infected MSMs [8,18,23,[25][26][27][29][30][31][33][34][35][36]. Recent PHE data demonstrated a 21% increase in new HIV infections amongst MSMs in London since 2011 [20].…”
Section: Discussionmentioning
confidence: 93%
“…Infections in HIV-infected individuals were predominately due to genotype 1a viruses and found only in males possibly reflecting un-reported sex between men. In addition to drug use, the observation of transmission in known HIV positives is not surprising with recent studies from high income countries have demonstrated a high incidence of recent HCV infections in HIV-infected MSMs [8,18,23,[25][26][27][29][30][31][33][34][35][36]. Recent PHE data demonstrated a 21% increase in new HIV infections amongst MSMs in London since 2011 [20].…”
Section: Discussionmentioning
confidence: 93%
“…Permucosal (particularly sexual) transmission is the predominant route of HCV acquisition among MSM, especially in HIV-infected individuals [53,83]. Use of mucosally administered recreational drugs (e.g., methamphetamines, ketamine, gammahydroxybutyrate, lysergic acid diethylamide) [62,[84][85][86][87] and high-risk traumatic sex practices, particularly unprotected anal intercourse, enema use prior to receptive anal intercourse, rectal trauma with bleeding, fisting, and group sex [58,68,72,84,85,87,88], have been identified as important behavioural risk factors for HCV transmission among MSM.…”
Section: Risk Factors For Hcv Acquisitionmentioning
confidence: 99%
“…These data indicate that the sexual route is indeed an important route of transmission for HCV, a fact corroborated by other authors in Brazil and the United States. 6,15 Some studies, such as those by Vandelli et al, Bradshaw et al and Witt et al,[36][37][38] also reported the importance of this route. This fact has been the subject of discussion in the literature, with studies indicating the importance of this route mainly among men who have sex with men that do not use drugs.…”
Section: Discussionmentioning
confidence: 99%